DISTANCE BASED ANALYSIS FOR DETECTION OF INTRUSIONS AND ANOMALIES (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
An Intrusion Detection System (IDS) is one of these layers of defense against malicious attacks. In IDS a stream of data is inspected and rules are applied in order to determine whether some attack is taking place. Intrusion Detection Systems typically operate within a managed network between a firewall and internal network elements. This paper discusses the intrusion detection using data mining techniques such as classification, association and clustering. In this paper we mainly focused on clustering techniques and outlier detection.